E-MODULES DEVELOPMENT OF INDEPENDENT WAR HISTORY IN JEMBER BASED INQUIRY USING ADDIE MODEL FOR SENIOR HIGH SCHOOL GRADE XI OF SOCIAL CLASS - Galih Widodo; Mohamad Na'im; Sumardi Sumardi (JURNAL HISTORICA, 2020)
Historical Learning using E-Module of Independence War History in Jember based Inquiry. This module is designed specifically to be used in Historical learning process. Historical Learning taught by educators to the learners is still within the national scope. The purpose of this research is: to produce a product in the form of electronic module based on Inquiry about the history of Independence War in Jember for senior high school grade XI of social class which is validated and proper to be used in Historical Learning, improving the effectiveness of learners' self-learning on Historical learning. This study used ADDIE model which consists of 5 steps, namely: (1) Analysis, (2) Design, (3) Develop, (4) Implementation, and (5) Evaluation. The resulting product, then validated by subject matter expert, linguist and design expert in a row showed: (1) the value of 96% belongs to "very good" category; (2) 94% of "very good" and (3) 98% of "very good" category. User test results get 98% of "very good" category. The results of small group trials and field trials showed: (1) 55.5% was categorized as "moderate" effectiveness; (2) 78.28% was categorized as "high" effectiveness. It can be concluded that E-Modules Development of Independence War History in Jember based Inquiry in the Historical Learning was effective for senior high school grade XI of social class. Keywords: Development of E-Module, History of Independence War in Jember, Inquiry